Nano-structured gas sensing materials for ammonia detection with special emphasis on medical applications (Indian Journal of Engineering and Materials Sciences (IJEMS), 2024)
Ammonia, a highly toxic gas which is known for its wide industrial usage, is now gaining importance as a biomarker for quite a few terminal diseases. Thereby, the research for a sensitive and highly selective ammonia gas sensor is gaining a whooping momentum these days. A brief study on importance and various sources of ammonia gas is recapitulated in this review along with elaboration of ammonia as a biomarker for clinical applications embracing renal and hepatic diseases. In addition, developments in nanotechnology based sensors for ammonia sensing is summarized in depth, emphasizing on metal-oxide semiconductor (MOS) based, polymer based and carbon nanomaterial based gas sensors. This review brings into limelight the importance of sensing very low concentration of ammonia. The performance of a wide range of MOS, polymer, and carbon nanomaterial based sensors is summarized in minute detail which will help researchers in attaining a quick analysis of state of art sensors to meet the needs of their intended application areas.